Perceptions And Attitudes of Saudi Arabia University Students Towards Adopting WhatsApp As Students-teachers’ Interactive Tool - Albloy, Amir Mohammed; Mohamed, Wijdan Mohieldeen (Advances in Social Sciences Research Journal, 2019)
This study was mainly grounded in the researchers’ personal experience of using WhatsApp as an interaction tool in an English classroom. This platform was used to enhance the communicative interaction between the students and their teachers. WhatsApp group was created during the first semester in 2018/2019 at the College of Science and Arts at Najran University - Branch of Sharurah, and the College of Sciences & Arts at Qassim University - Branch of Alasyah. The participants were bachelor degree students of English. The study employed a quantitative exploratory research approach, whereby a questionnaire was distributed to students who used WhatsApp as an interactive tool in their course of study. Data was obtained through a questionnaire with (40) purposively selected students of WhatsApp group. Data were analyzed quantitatively based on the SPSS program. The results show that WhatsApp had a positive effect in enhancing interaction between students and their teachers, WhatsApp makes interaction between teachers & their students easier than in the classroom. As a result, shy students can freely communicate & interact through WhatsApp with each other and their teachers, WhatsApp creates a friendly relationship between students and their teacher, and WhatsApp is an efficient tool of interaction in cases of distant learning. Therefore, student-teacher interaction becomes more effective in WhatsApp than inside the classroom.